Intraoperative Hypothermia and Post-Operative Anesthesia Recovery in Patients Age Above 65 Years Undergoing Abdominal Surgery - Maqsood Ahmed Siddiqui, Muhammad Taqi, Muhammad Suleman, Pardeep Kumar, Tabinda Qamar, Syed Lareb Ali Shah (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate the impact of hypothermia on post-anesthesia recovery time in patients above 65 years’ age undergoing abdominal surgery. Methodology: This cross sectional study was conducted on 300 patients who underwent abdominal surgery at LUHMS between October 2022 and October 2023. Temperatures of nasopharynx was recorded at the end of anesthesia induction (T0), and subsequently T1 at 0.5 hours, T2 at 1 hour, T3 at 1.5 hours, T4 at 2 hours, T5 at 2.5 hours, T6 at 3 hours, T7 at 3.5 hours, T8 at 4 hours, T9 at 4.5 hours, T10 at 5 hours, T11 at 5.5 hours, and T12 at 6 hours after the start of anesthesia. Results: The prevalence of adverse events (hypoxemia, nausea or vomiting, shivering) was high in patients with Hypothermia as compared to Non-Hypothermic patients. In hypothermia Group, hypoxemia, nausea/vomiting, and shivering were 46.4%, 18.7%, and 21.1%, respectively. Whereas, in Non-hypothermia Group, hypoxemia, nausea/vomiting, and shivering were 44.0%, 15.4%, and 17.6%, respectively. The mean time of anesthesia recovery of Hypothermia Group was higher than the Non-hypothermia Group, 98.16±5.06 minutes, and 96.69±6.39 minutes, respectively. Conclusion: Intraoperative hypothermia incidence remained high in patients with old age who underwent abdominal surgery, even after active warming. This mild hypothermia led to prolong anesthesia recovery time and shivering incidence. Keywords: Intraoperative hypothermia, Anesthesia recovery, Abdominal surgery, Elderly patients, Shivering